THE DEATH OF EXPERTISE - Rizkia Annisa Fitri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The death of expertise is an attack on the already established knowledge and adverse effects of half-half information in the community from the presence of Google, Wikipedia and blogs, many laymen who tend to degrade intellectually and advice from Experts. So feel quite satisfied with the information obtained from the media without the want to prove the truth and do not want to learn to find out. As if throwing science, damaging practices, and not willing to develop new science. Again the citizens were reluctant and felt already had enough information to make a decision. The death of expertise is not only the rejection of the already established knowledge, but the rejection of science and and the impartial rationality that is the basis of modern civilization. Most of the responses were shown against the presence of the Internet as a biang. Too simple, or lest this is just an anxiety among professional circles that occurs whenever there is a social or technological change. Without being denied, it is also possible that the death of expertise is a sign of progress.